VD_FINDINFO Jug / 2012 / 160 vom 18. Juni 2012 - VD Tribunal cantonal (2012)
JUSTE MOTIF, RÉSILIATION IMMÉDIATE, CONTRAT DE TRAVAIL, SUBROGATION LÉGALE | 337 al. 2 CO, 337 al. 3 CO, 337 CO, 337c al. 1 CO, 337c al. 3 CO, 337c CO, 49 CO, 29 al. 2 LACI